2015
DOI: 10.1007/s11356-015-5464-9
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium exposure and risk of pancreatic cancer: a meta-analysis of prospective cohort studies and case–control studies among individuals without occupational exposure history

Abstract: Pancreatic cancer is one of the most deadly types of cancer for both genders. Classified as a human carcinogen, cadmium has been related to diverse cancers. However, the association between cadmium exposure and the risk of pancreatic cancer is still unclear. We quantitatively reviewed the observational studies on the association of cadmium exposure with pancreatic cancer risk among individuals without occupational exposure history published through July 2014 in PubMed by using a fixed–effects model. Four prosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 44 publications
4
27
0
Order By: Relevance
“…Cadmium and lead were particularly high in KRAS wild‐type cases, lower in KRAS mutated cases, and much lower in controls. This pattern is in line with studies that identified cadmium and lead as important risk factors for developing PDAC (Amaral et al ; Chen et al ; Kriegel et al ; Luckett et al ). For cadmium, both KRAS mutational situations exhibited similar aORs in case–control comparisons.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Cadmium and lead were particularly high in KRAS wild‐type cases, lower in KRAS mutated cases, and much lower in controls. This pattern is in line with studies that identified cadmium and lead as important risk factors for developing PDAC (Amaral et al ; Chen et al ; Kriegel et al ; Luckett et al ). For cadmium, both KRAS mutational situations exhibited similar aORs in case–control comparisons.…”
Section: Discussionsupporting
confidence: 90%
“…Lifestyle risk factors include tobacco smoking, heavy alcohol intake, and obesity (Hart et al ). Among environmental factors, PDAC has been linked with exposure to aromatic amines and to several trace elements such as arsenic, cadmium, and lead (Amaral et al ; Antwi et al ; Chen et al ; Hart et al ; Luckett et al ; Porta et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, exposure to hydrocarbons is the most extensively studied occupational risk factor for PanCA and is associated with a 2–8 fold enhanced risk [16, 38]. Although the heavy metal relationship to PanCA was previously contested, recent reports have demonstrated that individuals with high exposure to cadmium, arsenic, and lead have a significantly higher risk for developing PanCA [16, 39]. Interestingly, cadmium exposure has been reported to be positively associated with PanCA in men, but not in women [39].…”
Section: Risk Factorsmentioning
confidence: 99%
“…Although the heavy metal relationship to PanCA was previously contested, recent reports have demonstrated that individuals with high exposure to cadmium, arsenic, and lead have a significantly higher risk for developing PanCA [16, 39]. Interestingly, cadmium exposure has been reported to be positively associated with PanCA in men, but not in women [39]. These data warrant more thorough investigations including gender differences and underlying molecular mechanism to determine the role of cadmium in pancreatic cancer.…”
Section: Risk Factorsmentioning
confidence: 99%